Unusual Cases in Peritoneal Surface Malignancies - Canbay, Emel.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book has been designed to provide the full description of the comprehensive management of peritoneal surface malignancies which have originated from different primaries, such as breast cancer, small bowel cancers and imatinib resistant GISTosis and sarcomas and pseudomyxoma. The book provides the most up-to-date information on current approaches such as cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Given the increasing evidence that the patients who may benefit from this treatment modality avoid potential lethal course of these diseases, the book explores the application of these approaches to a number of types of malignancy. The first chapters explore Benign Multicystic Mesothelioma and Pseudomyxoma Peritonei arising from unusual primaries. Among other explored topics are peritoneal metastases from serous papillary uterine carcinoma, sarcoma and from unusual origins. This book is valuable for surgical oncologists who deal with the management of peritoneal surface malignancies.
Benign Multicystic Mesothelioma -- Pseudomyxoma Peritonei arising from different origin rather than appendix and ovary -- Colorectum -- Fallopian tube -- Duodenum -- Small bowel -- Pancreas -- Desmoplastic small round cell tumour -- Uterine sarcoma -- Peritoneal metastases from breast cancer.-Peritoneal metastases from small bowel adenocarcinoma -- Peritoneal metastases from Imatinib resistant GISTosis -- Peritoneal metastases from serous papillary uterinecarcinoma -- Peritoneal metastases from unusalorigins -- Pancreas -- Gallbladder -- Liver -- Adrenal -- Esophagus -- Peritoneal metastases from sarcoma -- Peritoneal metastases from unusual miscellaneous tumours -- Retroperitoneal mullerian adenocarcinoma -- A giant mesentery malignant solitary fibrous tumour.
Keywords: Medicine; Oncology; Surgery; Medicine & Public Health; Oncology; Surgery